The Mutational, Epigenetic, and Transcriptional Effects Between Mixed High-Energy Particle Field (CR) and 7Li-Ion Beams (LR) Radiation in Wheat M1 Seedlings - Li, Bo; Zhao, Linshu; Zhang, Shuo; Cai, Haiya; Xu, Le; An, Bingzhuang; Wang, Rong; Liu, Gang; He, Yonggang; Jiao, Chunhai; Liu, Luxiang; Xu, Yanhao (Frontiers in Plant Science, 2022)
Ionizing radiation (IR) is an effective approach for mutation breeding. Understanding the mutagenesis and transcriptional profiles induced by different mutagens is of great significance for improving mutation breeding efficiency. Here, using RNA sequencing and methylation-sensitive amplification polymorphism (MSAP) approaches, we compared the genetic variations, epigenetics, and transcriptional responses induced by the mixed high-energy particle field (CR) and 7Li-ion beam (LR) radiation in M1 seedlings of two wheat genotypes (Yangmai 18 and Yangmai 20). The results showed that, in both wheat genotypes, CR displayed significantly a higher mutation efficiency (1.79 x 10-6 /bp) than that by LR (1.56 x 10-6 /bp). The induced mutations were not evenly distributed across chromosomes and varied across wheat genotypes. In Y18 M1, the highest number of mutations were detected on Chr. 6B and Chr. 6D, whilst in Y20 M1, Chr. 7A and Chr. 3A had the highest mutations. The transcript results showed that total of 4,755 CR-regulated and 1,054 LR-regulated differentially expressed genes (DEGs) were identified in the both genotypes. Gene function enrichment analysis of DEGs showed that these DEGs overlapped or diverged in the cascades of molecular networks involved in ‘phenylpropanoid biosynthesis’ and ‘starch and sucrose metabolism’ pathways. Moreover, IR type specific responses were observed between CR an LR irradiation, including specific TFs and response pathways. MSAP analysis showed that DNA methylation level increased in LR treatment, while decreased at CR. The proportion of hypermethylation was higher than that of hypomethylation at LR, whereas a reverse pattern was observed at CR, indicating that DNA methylation plays critical roles in response to IR irradiation. All these results support that the response to different IRs in wheat includes both common and unique pathways, which can be served as a useful resource to better understand the mechanisms of responses to different IRs in other plants.